Digital technologies for health education practices with children and adolescents - Silveira, Andressa da; Cazuni, Mariana Henrich; da Silva, Bruna Cardozo; Balk, Rodrigo Souza; dos Santos, Lairany Monteiro (Disciplinarum Scientia | Saúde, 2023)
Introduction: the use of digital technologies for health education practices with children and adolescents began to be used on a large scale, based on the need for social distancing generated by the COVID-19 pandemic. Objective: to know the perception of university students about the use of digital technologies for health education practices with children and adolescents. Method: qualitative, descriptive research, with university students belonging to nursing, physiotherapy and nutrition courses with previous experiences in research and extension, from the northwest region and the border of southern Brazil. Data collection took place in two stages, through a script prepared in Google Docs® for the purpose of characterizing the participants and the second stage through structured interviews in Google Meet®. The utterances were transcribed and subjected to thematic content analysis. Results: Two categories emerged “Use of digital media for education in times of pandemic” and “Use of digital technologies by children and adolescents”. Final considerations: from the perspective of university students, the use of digital technologies starts earlier and earlier, and they understand that health education practices through digital media were essential after the pandemic, for maintaining the bond, guidance, communication and autonomy for the care of children and adolescents.